Factor affecting the adaptability of expatriates / Muhammad Asnawi Ab Azis and Shazwani Saiful - Ab Azis, Muhammad Asnawi; Saiful, Shazwani (Faculty of Business and Management, 2015)
Hire expatriate allows the knowledge transfer from the expatriate to the organization. Nowadays, many companies using this method to enhance the productivity and management in the organization. However, if expatriates are not able to adapt with the surrounding, their performance will be below the par thus the knowledge that need to be transferred to local employees failed. There is yet to be a study that defines factors that affect the adaptability of the expatriates. The study also attempts to identify the level of expatriate’s adaptability and to investigate the relationship between openness, sociability, self-management, self-monitoring and motivation with adaptability. Based on the findings, the study was conducted to enhance our knowledge about expatriate’s adaptability. We were focusing on individual as our unit analysis in Petronas KLCC. The populations were expatriates in Petronas KLCC. The purpose of the studies is causal study which is we will describe the cause and effect or more factor that causing the problem. For the type of investigation, this study setting is known as non-contrived which is in the artificial setting. For the type of investigation, we use correlational study, which is focus on to identify the important factor associated with the problem. In addition, this study was conducted in the natural environment with minimum interference. This study setting is non-contrived which is artificial setting. The researchers has been collected 100 questionnaires back and used SPSS system version 22 to carry out the data analysis.